Yamato-793592: The first enstatite achondrite (aubrite) in the Yamatometeorite collections - Yanai, Keizo (National Institute of Polar Research, 1992)
P(論文) The first aubrite in the Yamato meteorite collections has been identified as a result of the recent initial processing at the National Institute of Polar Research (NIPR), Tokyo. Yamato-793592(Y-793592) is the only aubrite recovered so far among about 6000 classified specimens of the Yamato collections. Y-793592 is a friable small stone weighing 32g, with a white interior covered by a small amount of black fusion crust. It shows the typical brecciated texture and consists mostly of larger angular, white pyroxene (enstatite), less plagioclase and traces of olivine, with some opaque grains (blackish brown color). The constituent minerals of Y-793592 are almost pure Mg-pyroxene (enstatite), pure Mg-olivine (forsterite), sodic plagioclase, and small amounts of opaque phases such as Ni-poor metal, daubreelite, and troilites with highly variable compositions. departmental bulletin paper